The Role of Bhabinkamtibmas Polsek Tanjung Karang Barat in Economic Improvement Through The Kampung Tangguh Pinang Jaya Program - M Alvin Royantara (Advances in Police Science Research Journal, 2021)
This research is motivated by the covid-19 pandemic which has lowered the economy in Indonesia. Therefore, problem solving efforts are needed to improve the economy in the region. The purpose of this research is to explain the kampung tangguh pinang jaya program in an effort to improve the economy in the legal area of the Tanjung Karang Barat Police, the role of Bhabinkamtibmas in improving the economy through the village tough pinang jaya program and the factors that influence it. The analysis knife in this research is management theory and SWOT analysis, role theory, tough village concept, Bhabinkamtibmas concept, and Kamtibmas concept. This research was conducted with a qualitative approach with field research research methods, which were then carried out through interviews, observation and document study and analyzed by reducing data, presenting data and verifying data. As well as with reduction techniques, presentation, verification, and drawing conclusions. The results of this study indicate that the potential impediments to the kampung tangguh pinang jaya program come from human resources and the city government. The role of Bhabinkamtibmas in improving the economy through the kampung tangguh pinang jaya program, among others, is through the implementation of the sambang (Door to door) for all Pinang Jaya villagers and solving problems of problems in Pinang Jaya Village. The factors that influence the role of Bhabinkamtibmas in improving the economy through the kampung tangguh pinang jaya program come from the lack of community support, low awareness of the community, and inadequate facilities and infrastructure. The suggestion in this research is that Bhabinkamtibmas should be able to coordinate and communicate with the community, increase the allocation of resources needed. Then create a work appraisal system aimed at identifying and measuring performance, Giving Rewards and Punishments to Bhabinkamtibmas members that are more objective and sustainable. And in the future, Bhabinkamtibmas members reside in their jurisdiction so that they can act quickly and be more able to receive valid information.